2016
DOI: 10.1017/s0967199415000696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fifth day (D5) or sixth day (D6) frozen–thawed blastocysts on neonatal outcomes

Abstract: This study aimed to compare the neonatal outcomes of transplanted fifth day (D5) or sixth day (D6) frozen-thawed blastocysts, aiming to provide guidance when choosing blastocyst recovery methods. The clinical data of 1109 patients that were performed for recovered blastocyst transplantation, as well as the data of 515 patients who had already delivered were analyzed retrospectively. The patients were divided into single- or twins-birth groups according to blastocyst formation time (D5 or D6) and the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
5
15
0
1
Order By: Relevance
“…Ferreux et al also reported similar EMRs between D5 and D6 cryopreserved blastocyst transfers [15]. However, similar to our study, Wang et al reported a higher EMR in the D6 blastocysts than in the D5 blastocysts(16.4% vs. 11.9%), although not statistically significant [19].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Ferreux et al also reported similar EMRs between D5 and D6 cryopreserved blastocyst transfers [15]. However, similar to our study, Wang et al reported a higher EMR in the D6 blastocysts than in the D5 blastocysts(16.4% vs. 11.9%), although not statistically significant [19].…”
Section: Discussionsupporting
confidence: 85%
“…Some reports showed equivalent outcomes between blastocysts formed and cryopreserved on day 5 (D5 blastocysts) and blastocysts formed and cryopreserved on day 6 (D6 blastocysts) [11][12][13][14]. Meanwhile, there is a growing body of evidence indicating that the CPR, IR, and live birth rate (LBR) with D5 blastocysts are higher than with D6 blastocysts in FET cycles [15][16][17][18][19][20]. Therefore, whether the day of blastocyst formation affects clinical outcomes remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, 23 studies were included in the following meta-analyses. 4,6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The main characteristics and assessment for risk of bias of the included studies are presented in Table 1.…”
Section: Results Of the Searchesmentioning
confidence: 99%
See 1 more Smart Citation